Setting evolutionary‐based conservation priorities for a phylogenetically data‐poor taxonomic group (Scleractinia). (22nd January 2015) - Curnick, D. J.; Head, C. E. I.; Huang, D.; Crabbe, M. J. C.; Gollock, M.; Hoeksema, B. W.; Johnson, K. G.; Jones, R.; Koldewey, H. J.; Obura, D. O.; Rosen, B. R.; Smith, D. J.; et al.
<x xml:space="preserve">Abstract</x> Read the Commentaries on this Feature Paper: Valuing species on the cheap; Conservation prioritization in the context of uncertainty; Regional specific approach is a next step for setting evolutionary‐based conservation priorities in the scleractinian corals and the Response from the authors: Setting evolutionary based conservation priorities for a phylogenetically data‐poor taxonomic group (Scleractinia): response to the commentaries